Influence of H-bonding on self-assembly and tunable dual-emission of carbazole-based Zn(II)-terpyridine metallocycles - Sun, Handong (2014)
Two carbazole derivatives with terpyridine units attached to the 3,6-positions are synthesized, 1 with a hydrogen at the 9-position and 2 bearing a dodecyl chain there, to evaluate the influence of H-bonds on their self-assembly behavior with metal ions. The unalkylated derivative 1 assembles with zinc ions to form a single product identified by NMR, electrospray ionisation mass spectrometry (ESI-MS), and X-ray photoelectron spectroscopy (XPS) as a pentametric metallocycle (Zn-1), whereas 2 forms a mixture of two assemblies (Zn-2). The pentamer Zn-1 shows tunable dual emission in the blue and green regions by varying the solvent and excitation wavelength, and molecular packing studies by powder X-ray diffractometry (XRD), transmission electron microscopy (TEM), polarising optical microscopy (POM), and atomic force microscopy (AFM) reveals a high propensity to form ordered layers. A fluorescence quenching experiment of electron-rich Zn-1 with C60 shows a high association constant of Ksv = 3.2 × 105m−1, suggesting effective charge transfer between Zn-1 and C60 molecules.